(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
In today’s digital era, the widespread dissemination of unreliable information causes confusion and misguidance, highlighting the need for swift identification of online assertions to enhance social network credibility and mitigate information pollution. Ensuring the accuracy of information, particularly from dubious sources, is crucial, with efforts focused on creating educational materials that foster awareness and critical thinking to curb its dissemination. This study aims to determine the fact- checking strategies of the respondents. The study utilized a quantitative approach employing descriptive design to describe the fact-checking strategies used by the respondents and their comparison when grouped according to their sex and grade level. The researchers gathered data from 144 Junior High School students using a survey questionnaire. Weighted mean and Pearson Product Moment Correlation were the statistical tools utilized. The results revealed that the respondents use fact-checking strategies, particularly checking information if it b seems credible. They also consider the headline or main message along with the source of the information and the relevance of the information they are reading. While their level of using fact-checking strategies is high, there is a need to improve this area since it is not at the optimal level. Furthermore, there is a significant difference when they are grouped according to grade level, wherein students in the higher grade level have higher usage of these strategies than lower grade levels. There is no significant difference between males and females when it comes to using these fact-checking strategies. The findings indicate that the respondents are already utilizing various strategies to check if the information is credible, but there is still a need to enhance their usage. Developing strong fact-checking skills is crucial for students as they progress academically. The researchers recommend that a fact- checking advocacy material be disseminated to students to further improve their usage of these strategies.